2015
DOI: 10.4067/s0718-915x2015000300006
|View full text |Cite
|
Sign up to set email alerts
|

Study of stud shear connectors behaviour in composite beams with profiled steel sheeting

Abstract: Study of stud shear connectors behaviour in composite beams with profiled steel sheeting Estudio del comportamiento de conectores tipo perno en vigas compuestas con lámina nervadaJorge Douglas Bonilla Rocha (Main and Correspondent Author) AbstractThis work presents an FE study concerning the prediction of the shear resistance of headed stud connectors in composite beams with profiled steel sheeting subjected to static load. To confirm the FE simulation for the determination of the shear resistance of stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…This research was reported by the authors in Arrayago et al [18], and it was concluded that in general expressions in [16,17] are applicable to ferritic stainless steel decks, although some modified expressions can be used if higher accuracy is required in the design. Figure 1 Trapezoidal steel deck in composite floor slab [19] The behaviour of composite floor slab systems has been systematically investigated during the last decades through different experimental and numerical studies [20][21][22][23][24][25][26][27], and the fire performance of such structures has also been carefully characterized [28][29][30]. In addition to the punching shear failure, the failure of composite slabs is governed by three major failure modes, as shown in Figure 2, which are bending (for considerably high shear spans L s ), vertical shear (for low shear spans) and longitudinal shear (for intermediate values of L s ), related to the relative slip between the steel deck and the concrete at supports, where the shear span L s is the distance from the point of application of concentrated force to its respective reaction force.…”
Section: Introductionmentioning
confidence: 99%
“…This research was reported by the authors in Arrayago et al [18], and it was concluded that in general expressions in [16,17] are applicable to ferritic stainless steel decks, although some modified expressions can be used if higher accuracy is required in the design. Figure 1 Trapezoidal steel deck in composite floor slab [19] The behaviour of composite floor slab systems has been systematically investigated during the last decades through different experimental and numerical studies [20][21][22][23][24][25][26][27], and the fire performance of such structures has also been carefully characterized [28][29][30]. In addition to the punching shear failure, the failure of composite slabs is governed by three major failure modes, as shown in Figure 2, which are bending (for considerably high shear spans L s ), vertical shear (for low shear spans) and longitudinal shear (for intermediate values of L s ), related to the relative slip between the steel deck and the concrete at supports, where the shear span L s is the distance from the point of application of concentrated force to its respective reaction force.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of experimental studies are on precast structural elements precast beam-column joints without transverse beams and slabs (Bonilla, Bezerra, Larrúa Quevedo, Recarey Morfa, & Mirambell Arrizabalaga, 2015;Saleem, Khurram, Amin, & Khan, 2018;Ma, Jiang, & Wang, 2019). However, seismic performance and mode of failures of precast beamcolumn and precast beam-slab are directly affected by existance of the transverse beams and slabs (Parastesh, Hajirasouliha, & Ramezani, 2014;Chen, Yan, & Gao, 2012;Choi, Choi, & Choi, 2013;Yuksel et al, 2015;Köken & Köroglu, 2014;Yardim, 2018).…”
Section: Introductionmentioning
confidence: 99%